Psykisk helsearbeideres erfaringer med å jobbe i små kommuner i Nordland - Toril Beate Masvie; Siri Ytrehus (Septentrio Academic Publishing, 2013)
Abstract  "Mental health workers' experiences of working  in small municipalities in Northern Norway This study addresses the experience of mental health workers working in small municipalities in northern Norway. The study is based on qualitative interviews and had special focus on how the context influenced their professional role and role as citizens. The informants emphasized both positive and negative aspects of their work, but the negative aspects were most prominent in the interviews. On the one hand they experienced high degree of independency and possibility of close relationships to the patients due to transparency, but on the other hand also professional loneliness.  The relationship to the patients was multifaceted. The boundary between their professional role and the role as a citizen was difficult to maintain. The professional role could affect their private life and the role and relations they had in the community as a citizen. Some felt they had to withdraw from social networks and arenas which had been important to them.